2018
DOI: 10.1093/nar/gky193
|View full text |Cite
|
Sign up to set email alerts
|

Mbd2-CP2c loop drives adult-type globin gene expression and definitive erythropoiesis

Abstract: During hematopoiesis, red blood cells originate from the hematopoietic stem cell reservoir. Although the regulation of erythropoiesis and globin expression has been intensively investigated, the underlining mechanisms are not fully understood, including the interplay between transcription factors and epigenetic factors. Here, we uncover that the Mbd2-free NuRD chromatin remodeling complex potentiates erythroid differentiation of proerythroblasts via managing functions of the CP2c complexes. We found that both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 69 publications
(66 reference statements)
1
22
0
Order By: Relevance
“…Therefore, targeting MBD2 specifically at its IDPR would be a promising approach to the development of antimetastatic agents by inhibiting its DOT-based PPI with p66α that is essential for the integration of CRC and thus for its critical function in EMT. In addition, no noticeable adverse effects displayed by MBD2 inhibitors can be expected from the fact that down-regulation of MBD2 expression is essential for normal cell differentiation ( 33 ), and yet, MBD2 knockout ( MBD2 −/− ) mice exhibit normal survival and reproduction ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, targeting MBD2 specifically at its IDPR would be a promising approach to the development of antimetastatic agents by inhibiting its DOT-based PPI with p66α that is essential for the integration of CRC and thus for its critical function in EMT. In addition, no noticeable adverse effects displayed by MBD2 inhibitors can be expected from the fact that down-regulation of MBD2 expression is essential for normal cell differentiation ( 33 ), and yet, MBD2 knockout ( MBD2 −/− ) mice exhibit normal survival and reproduction ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding employment of MEL cells as a cellular model of erythropoiesis [7,8,9,10,11,12,13,14,15,16,17], we successfully confirmed that Mbd2 and p66α have different roles in erythroid differentiation and tumorigenicity in vivo (Figure 2). Therefore, our MEL cell-transfused allograft model provides a valuable tool to discriminate between erythroid differentiation and tumorigenic potential of erythroleukemia by examining splenomegaly and circulating cells in the blood.…”
Section: Discussionmentioning
confidence: 73%
“…We found earlier that the Mi-2/nucleosome remodeling deacetylase (NuRD) chromatin remodeling complex (CRC) potentiates erythroid differentiation of proerythroblasts by regulating functions of the CP2c complex [7]. CP2c (also known as TFCP2, CP2, α-CP2, LSF, and LBP-1c) is a ubiquitously expressed transcription factor [8,9,10], exerting a critical role in globin expression and erythropoiesis [11,12,13,14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the NuRD complex become MBD2 free during erythropoiesis. Therefore, the complex that acts as a transcriptional coactivator may have different configurations to facilitate gene activation [ 85 ].…”
Section: Gata-1 Interacts With Hdac1 Containing Nurd Complex For Amentioning
confidence: 99%